Lilly comes to question 2017 on her calculus final:
∫ − 1 1 1 + x 2 d x
She thinks to herself, "This looks like a standard u-substitution question!" and begins to work it out. "Let's see. I'm going to rewrite the integral by letting u = 1 + x 2 and changing the limits of integration.
For x = − 1 , we have u = 1 + ( − 1 ) 2 = 2 . For x = 1 , we have u = 1 + ( 1 ) 2 = 2 . So our new integral is..."
∫ u = 2 u = 2
"Oh wait!" she interjects, stopping herself. "The limits of integration are the same so the integral must equal 0 no matter what the integrand is!" However, she realizes that f ( x ) = 1 + x 2 > 0 ∀ x . "As long as b > a , ∫ a b 1 + x 2 d x must always be positive. What did I do wrong?"
Can you help Lilly? If the value of the definite integral can be expressed as m + sinh − 1 ( n ) for positive, square-free integers ( m , n ) , find m + n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I did the same till the l n ( 1 + 2 ) step. Then I couldn't find a way to get into hyperbolic sine. Thanks for that clarification!
∫ − 1 1 1 + x 2 d x
Since the function 1 + x 2 is even, the above integral can be written as - I = 2 ∫ 0 1 1 + x 2 d x l e t sinh ( u ) = x ⟹ cosh ( u ) d u = d x . ⟹ I = 2 ∫ x = 0 1 1 + sinh 2 ( u ) cosh ( u ) d u = 2 ∫ x = 0 1 cosh 2 ( u ) cosh ( u ) d u . ⟹ 2 ∫ x = 0 1 cosh 2 ( u ) d u ⟹ I = 2 ∫ x = 0 1 2 cosh ( 2 u ) + 1 d u ∣ ∣ ∣ ∣ cosh ( 2 u ) = 2 cosh 2 ( u ) − 1 ⟹ cosh 2 ( u ) = 2 cosh ( 2 u ) + 1 ⟹ I = 2 ⋅ 2 1 ∫ x = 0 1 cosh ( 2 u ) + 1 d u = ( 2 sinh ( 2 u ) + u ) ∣ ∣ ∣ ∣ x = 0 1 ⟹ I = ( 2 2 sinh ( u ) cosh ( u ) + u ) ∣ ∣ ∣ ∣ x = 0 1 ∣ ∣ ∣ ∣ sinh ( 2 u ) = 2 sinh ( u ) cosh ( u ) Writing I in terms of x we get - I = ( x 1 + x 2 + sinh − 1 ( x ) ) ∣ ∣ ∣ ∣ x = 0 1 ∣ ∣ ∣ ∣ sinh ( u ) = x , cosh ( u ) = 1 + sinh 2 ( u ) ⟹ cosh ( u ) = 1 + x 2 ⟹ I = ( 1 ⋅ 1 + 1 2 + sinh − 1 ( 1 ) − 0 ⋅ 1 + 0 2 − sinh − 1 ( 0 ) ) = ( 2 + sinh − 1 ( 1 ) ) ⟹ I = 2 + sinh − 1 ( 1 ) ⟹ m = 2 , n = 1 ⟹ m + n = 3
∫ 1 + x 2 d x
Substitute t = x + 1 + x 2 x = 2 t t 2 − 1 d x = 2 t 2 t 2 + 1
∫ 1 + x 2 d x = 4 1 ∫ t 3 t 4 + 2 t 2 + 1 d t = 8 t 2 + 2 l n ∣ t ∣ − 8 t 2 1 = 8 ( x + 1 + x 2 ) 2 + 2 l n ∣ x + 1 + x 2 ∣ − 8 ( x + 1 + x 2 ) 2 1
So, its value between -1 and 1 is 2 + l n ( 3 + 8 )
Considering 3 + 8 as 2 3 + 1 + 2 3 − 1 = 2 + 1
The value of the integral is 2 + l n ( 1 + 2 ) = 2 + sinh − 1 ( 1 )
So, m+n=2+1=3
Problem Loading...
Note Loading...
Set Loading...
The integral I = ∫ − 1 1 1 + x 2 d x is an even function. It should be I = 2 ∫ 0 1 1 + x 2 d x .
I = ∫ − 1 1 1 + x 2 d x = 2 ∫ 0 1 1 + x 2 d x = 2 ∫ 0 π / 4 1 + tan 2 θ sec 2 θ d θ = 2 ∫ 0 π / 4 sec 3 θ d θ = 2 ( 3 − 1 sec 3 − 2 θ tan θ ∣ ∣ ∣ ∣ 0 π / 4 + 3 − 1 3 − 2 ∫ 0 π / 4 sec 3 − 2 θ d θ ) = 2 + ∫ 0 π / 4 sec θ d θ = 2 + ln ( tan θ + sec θ ) ) ∣ ∣ ∣ ∣ 0 π / 4 = 2 + ln ( 1 + 2 ) = 2 + sinh − 1 1 As the integrand is even Let x = tan θ , d x = sec 2 θ d θ Note that 1 + tan 2 θ = sec 2 θ Using reduction formula See note 1 below. See note 2 below.
⟹ m + n = 2 + 1 = 3
Note 1:
I = ∫ sec x d x = ∫ tan x + sec x sec x tan x + sec 2 x d x = ∫ u 1 d u = ln u + C = ln ( tan x + sec x ) + C Let u = tan x + sec x , d u = ( sec 2 x + tan x sec x ) d x where C is the constant of integration.
Note 2:
sinh ( ln ( 1 + 2 ) ) ⟹ sinh − 1 1 = 2 e ln ( 1 + 2 ) − e − ln ( 1 + 2 ) = 2 1 + 2 − 1 + 2 1 = 2 1 + 2 − ( 2 + 1 ) ( 2 − 1 ) 2 − 1 = 2 1 + 2 − 2 + 1 = 1 = ln ( 1 + 2 )